2017
DOI: 10.1002/pros.23455
|View full text |Cite
|
Sign up to set email alerts
|

The orally active pterocarpanquinone LQB‐118 exhibits cytotoxicity in prostate cancer cell and tumor models through cellular redox stress

Abstract: LQB-118 is a developing and orally active pterocarpanquinone agent that effectively kills PCa cells through quinone reduction and ROS generation. The inhibition SOD1 expression enhances LQB-118 activity, presumably by impairing the cellular antioxidant response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our previous studies demonstrated the cytotoxic activity of the synthetic LQB-118 compound in several types of cancer, including AML (25)(26)(27)(28)(29)(40)(41)(42)(43). Therefore, the present study aimed to investigate the antitumor effect of the LQB-118 compound particularly in cells resistant to cytarabine.…”
Section: Lqb-118 Exhibits Cytotoxicity Against Cytarabine-resistant C...mentioning
confidence: 96%
“…Our previous studies demonstrated the cytotoxic activity of the synthetic LQB-118 compound in several types of cancer, including AML (25)(26)(27)(28)(29)(40)(41)(42)(43). Therefore, the present study aimed to investigate the antitumor effect of the LQB-118 compound particularly in cells resistant to cytarabine.…”
Section: Lqb-118 Exhibits Cytotoxicity Against Cytarabine-resistant C...mentioning
confidence: 96%
“…Later, studies further confirm that miR-101-3p targets EZH2 and suppresses proliferation and migration of PCa cells [12,13]. After thoroughly reviewing published literature on PCa, we found that ten target genes including SOD1 [14], SUB1 [15], TIGAR [16], NR2F2 [17], RLIP76 [9], COX-2 [18], Glyoxalase 1 [19], ZEB1 [20], Slug [20] as well as EZH2 [11,13,21,22] were truly inhibited by miR-101-3p in PCa tissues or cells. Furthermore, we found that the target genes of miR-101-3p were enriched in many biological processes, such as positive regulation of transcription, intracellular signal transduction, protein autophosphorylation, activation of MAPKK activity.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies demonstrated that high SOD expression correlates with colon tumor aggressiveness and with resistance to cytotoxic drugs and radiotherapy [ 50 ]. The loss of SOD1 expression by siRNA knockdown significantly increased prostate cell sensitivity to cytotoxic agents, confirming SOD1 participation in cellular response and resistance [ 51 ]. Some evidence has indicated SOD1 overexpression in cancers maintaining cellular ROS below the crucial threshold [ 52 ].…”
Section: Resultsmentioning
confidence: 99%